Evaluation of Proclarix in the diagnostic work‐up of prostate cancer - Basil Kaufmann; Sharon Fischer; Alcibiade Athanasiou; Noémie Lautenbach; Anja Wittig; Uwe Bieri; Florian A. Schmid; Franz vonStauffenberg; Thomas Scherer; Daniel Eberli; Michael A. Gorin; Ralph Schiess; et al. (BJUI Compass, 2024)
Abstract Objectives The use of multiparametric magnetic resonance imaging (mpMRI) has been widely adopted in the diagnostic work‐up for suspicious prostate cancer (PCa) and is recommended in most current guidelines. However, mpMRI lesions are often indeterminate and/or turn out to be false‐positive on prostate biopsy. The aim of this work was to evaluate Proclarix, a biomarker test for the detection of relevant PCa, regarding its diagnostic value in all men before biopsy and in men with indeterminate lesions on mpMRI (PI‐RADS 3) during work‐up for PCa. Materials and Methods Men undergoing mpMRI‐targeted and systematic biopsy of the prostate were prospectively enrolled. The Proclarix test was evaluated for the detection accuracy of clinically significant PCa (csPCa) defined as Grade Group ≥ 2 and its association to mpMRI results. Further, Proclarix's performance was also tested when adapted to prostate volume (Proclarix density) and performance compared to PSA density (PSAD). Results A total of 150 men with a median age of 65 years and median PSA of 5.8 ng/mL were included in this study. CsPCa was diagnosed in 65 (43%) men. Proclarix was significantly associated with csPCa and higher PI‐RADS score (p < 0.001). At the pre‐defined cut‐off of 10%, Proclarix's sensitivity for csPCa was 94%, specificity 19%, negative predictive value 80% and positive predictive value 47%. Proclarix density showed the highest AUC for the detection of csPCa of 0.77 (95%CI: 0.69–0.85) compared to PSA, PSAD and Proclarix alone. Proclarix was able to identify all six csPCa in men with PI‐RADS 3 lesions (n = 28), whereas PSAD missed two out of six. At optimized cut‐offs, Proclarix density outperformed PSAD by potentially avoiding 41% of unnecessary biopsies. Conclusion Proclarix demonstrates high sensitivity in detecting csPCa but may still result in unnecessary biopsies. However, Proclarix density was able to outperform PSAD and Proclarix and was found to be useful in men with PI‐RADS 3 findings by safely avoiding unnecessary biopsies without missing csPCa.